Miniaturized and improved method for Apparent Total N-Nitroso Compounds determination in beer - Tomáš Vrzal; Michaela Malečková; Jana Olšovská (Kvasný průmysl, 2021)
A miniaturized and improved method for Apparent Total Nitroso Compounds determination in liquid matrices was developed. The main improvement is based on a miniaturized and modified apparatus for chemical denitrosation of nitroso compounds by hydrogen bromide in a glacial acetic acid mixture. The reaction is carried out in a teflon reaction coil while the reaction product, gaseous nitric oxide, is drifted to a chemiluminescence detector by the flow of argon together with a vacuum obtained by the detector's oil pump. The apparatus significantly increased the efficiency of the Apparent Total N-Nitroso Compounds determination (compared to the previous method), specifically, the dead volume of the apparatus was significantly decreased, and the effect of the reverse reaction was eliminated as well. The apparatus shortens the analysis time (1.4 min/injection), further it provides a lower detection limit (3 μg(N-NO)/l), quantification limit (10 μg(N-NO)/l), and method uncertainty (15%), and is simpler for the operation.